Increasing students’ learning activity and motivation in advanced mathematics through problem-based learning assisted by online learning media - Faren Hasna Hafizha; Z. Zukhrufurrohmah (Jurnal Pendidikan Profesi Guru, 2025)
Low participation and weak learning motivation often hinder students’ progress in advanced mathematics. This classroom action research investigated whether Problem-Based Learning (PBL) supported by online learning media could enhance Grade XI students’ learning activity and motivation at SMA Negeri 1 Malang, Indonesia. Quizizz and Wordwall served as platforms. Thirty-five students in class XI-3 participated in two cycles (planning, action, observation, reflection), each comprising two meetings. Data were collected through structured observations of activity and motivation, a motivation questionnaire, and a learning-implementation checklist, and were analyzed descriptively using percentages. Results showed consistent gains from Cycle 1 to Cycle 2: activity increased from 72% to 86%, observed motivation from 70% to 85%, and questionnaire motivation from 74% to 89%. The overall average rose from 75% to 87%, exceeding the success criterion (≥76%).